Variable transmittance optical laminate, method for manufacturing same, smart window, vehicle, automobile, wearable device, and window for construction
By using an ultraviolet barrier substrate and a near-ultraviolet protective layer in the variable transmittance optical laminate, combined with the conductive layer design on the polarizing plate, the field of view and energy saving problems caused by deterioration of the liquid crystal layer and fixed transmittance are solved. Achieve more efficient light management and life span.
Patent Information
- Application Number
- CN202410750912.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-13
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing optical laminates with variable transmittance are susceptible to near-ultraviolet damage after applying voltage, resulting in deterioration of the liquid crystal layer and affecting the life of the display. The fixed transmittance of traditional glass windows leads to limited view of the driver under different light conditions. And it is not energy-saving and efficient.
A variable transmittance optical laminate containing an ultraviolet barrier substrate, a polarizer and a near-ultraviolet protective layer was designed. By directly forming a conductive layer on the polarizing plate, it effectively shields the ultraviolet and near-ultraviolet rays, reduces the thickness and improves the transmission. Transmission rate in light mode.
It effectively prevents the deterioration of the liquid crystal layer, extends the life of the display, and improves the driver's field of vision adaptability and the energy-saving efficiency of the building through variable transmittance.
Smart Images

Figure CN119126424A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a variable transmittance optical stack, a method for manufacturing the same, and a smart window comprising the same. Background Art
[0002] Generally speaking, glass windows of mobile tools such as vehicles are often coated with external light blocking coatings. However, the transmittance of glass windows of conventional mobile tools is fixed, and the transmittance of external light blocking coatings is also fixed. Therefore, since the overall transmittance of the windows of such conventional mobile tools is fixed, accidents may occur. For example, if the overall transmittance is set low, then although there is no problem during the day when the surrounding light is sufficient, there is a problem that it is difficult for the driver and others to correctly view the surrounding conditions of the mobile tool in the case of insufficient surrounding light at night. In addition, if the overall transmittance is set high, there is a problem that it may cause glare to the driver and others during the day when the surrounding light is sufficient. In addition, glass windows of buildings and the like are often coated with external light blocking coatings to improve cooling and heating efficiency and achieve energy saving. In this case, if the transmittance is fixed, there is a problem of poor efficiency in energy saving, as in the case of mobile tools.
[0003] For this purpose, a variable transmittance optical stack has been developed that can change the transmittance of light when a voltage is applied. The variable transmittance optical stack is driven by applying a voltage to drive the liquid crystal so as to have a variable transmittance. In order to achieve variable transmittance, a target transmittance is achieved by having a liquid crystal layer whose phase changes according to the applied electric field. However, in reality, near-ultraviolet rays or ultraviolet rays can pass through the liquid crystal of the variable transmittance optical stack, and thus the liquid crystal layer is frequently degraded, thereby shortening the life of the display.
[0004] On the other hand, Korean Registered Patent Gazette No. 10-0416924 relates to a method for imparting an ultraviolet absorption function to a polarizing film with a polyvinyl alcohol film as a substrate and a polarizing film with an ultraviolet absorption function manufactured by the method, but when applied to a liquid crystal display device or a smart window including a polarizing plate, there are limitations in preventing degradation caused by ultraviolet rays and controlling transmittance after voltage is applied.
[0005] Therefore, the actual situation is that there is a need to develop a variable transmittance optical laminate that includes a polarizing plate and reduces transmittance when a voltage is applied to thereby excel in light resistance, and a smart window including the same.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Korean Registered Patent Gazette No. 10-0416924 Summary of the invention
[0009] Issues to be solved
[0010] In order to solve the above problems, the present invention intends to provide a variable transmittance optical laminate having excellent light resistance, maintaining transparency in the visible light region, and capable of preventing degradation of a liquid crystal layer by effectively blocking near ultraviolet rays.
[0011] The present invention also intends to provide a smart window including the above-mentioned variable transmittance optical laminate and a window for a car or a building to which the smart window is applied.
[0012] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and a person skilled in the art should be able to clearly understand other problems not mentioned based on the following description.
[0013] Solution to the problem
[0014] The present invention relates to a variable transmittance optical stack, which includes: a first polarizing plate; a first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate opposite to the first polarizing plate; a second transparent conductive layer formed on one surface of the second polarizing plate and opposite to the first transparent conductive layer; and a liquid crystal layer present between the first transparent conductive layer and the second transparent conductive layer, wherein the first polarizing plate includes an ultraviolet blocking substrate, a polarizer and a near-ultraviolet protective layer.
[0015] In the present invention, the first polarizing plate may be formed on the outer side facing the light source.
[0016] In the present invention, the first polarizing plate may be characterized in that an ultraviolet blocking substrate, a polarizer, and a near-ultraviolet protective layer are stacked in order from the outer side facing the light source.
[0017] In the present invention, the ultraviolet blocking substrate may be characterized in that a transmittance at a wavelength of 380 nm or less is 10% or less.
[0018] In the present invention, the ultraviolet blocking substrate may be characterized by comprising an ultraviolet blocking additive.
[0019] In the present invention, the ultraviolet blocking substrate may be characterized by comprising at least one selected from the group consisting of a polyester film, a cellulose film, a polyimide film, and a polycarbonate film.
[0020] In the present invention, the near-ultraviolet protective layer may contain one or more selected from near-ultraviolet absorbers and ultraviolet sensitizers.
[0021] In the present invention, the near-ultraviolet absorber may be characterized in that the maximum absorption wavelength is 390 nm to 430 nm.
[0022] In the present invention, the near-ultraviolet absorber may be characterized in that it is a cyanine compound.
[0023] In the present invention, the maximum absorption wavelength of the ultraviolet sensitizer may be 350nm to 400nm.
[0024] In the present invention, the ultraviolet sensitizer may be characterized in that it is an oxazole compound.
[0025] In the present invention, at least one of the first polarizing plate and the second polarizing plate may include one or more functional layers selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
[0026] In the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0027] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed to be in direct contact with one of the first polarizing plate and the second polarizing plate without including a separate substrate.
[0028] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed to be in direct contact with one of the first polarizing plate and the second polarizing plate by further including an easy-adhesion layer therebetween.
[0029] In the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may include one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0030] In the present invention, the liquid crystal layer may include one or more spacers selected from the group consisting of ball spacers and column spacers.
[0031] In the present invention, the variable transmittance optical laminate may further include at least one selected from the group consisting of a frame sealant, an alignment film, a sticking / adhesive layer, and an ultraviolet light absorbing layer.
[0032] Furthermore, the present invention relates to a method for producing the variable transmittance optical layered body.
[0033] Furthermore, the present invention relates to a smart window including the variable transmittance optical laminate.
[0034] In addition, the present invention may relate to a vehicle including the above-mentioned smart window, and may relate to a car in which the smart window is applied to at least one of the front window, rear window, side window, skylight and interior partition.
[0035] In addition, the present invention may relate to wearable devices, building windows, etc. that include the above-mentioned smart window.
[0036] Effects of the Invention
[0037] The variable transmittance optical laminate of the present invention has low transmittance in the ultraviolet and / or near-ultraviolet region and can effectively shield ultraviolet and / or near-ultraviolet light, thereby preventing degradation of the liquid crystal layer due to ultraviolet light and improving the problem of shortened display life.
[0038] Furthermore, according to the variable transmittance optical layered body of the present invention, since the conductive layer is directly formed on one surface of the polarizing plate without including a separate substrate for forming the conductive layer, the thickness can be significantly reduced compared to conventional optical layered bodies.
[0039] Furthermore, according to the variable transmittance optical layered body of the present invention, since the conductive layer is directly formed on one surface of the polarizing plate without including a separate substrate for forming the conductive layer, the transmittance in the light transmission mode can be improved compared to the conventional optical layered body.
[0040] In addition, by including the variable transmittance optical laminate of the present invention, it is possible to provide a high-quality smart window and a window for a car or a building to which the smart window is applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The structure of the first polarizing plate according to one embodiment of the present invention is shown.
[0042] Figure 2 A preferred stacking structure of a variable transmittance optical stack according to an embodiment of the present invention is shown.
[0043] Figure 3a to Figure 3c The light resistance evaluation observation results of the experimental examples are shown respectively. Specifically, Figure 3a It is a state where no light leakage is observed and the film remains opaque. Figure 3b This is a state where light leakage is partially observed. Figure 3c This is a state where light leakage is observed on the entire surface.
[0044] Explanation of symbols
[0045] 100: Transmittance variable optical laminate
[0046] 110-1: First polarizing plate
[0047] 111: UV blocking substrate
[0048] 112: Polarizer
[0049] 113: Near UV protection layer
[0050] 120-1: First transparent conductive layer
[0051] 110-2: Second polarizing plate
[0052] 120-2: Second transparent conductive layer
[0053] 130: Liquid crystal layer
[0054] A: Light source DETAILED DESCRIPTION
[0055] The present invention relates to a variable transmittance optical laminate capable of preventing degradation of a liquid crystal layer caused by ultraviolet rays by effectively shielding ultraviolet rays and / or near-ultraviolet rays, a method for manufacturing the same, and a smart window comprising the same. In more detail, the variable transmittance optical laminate comprises: a first polarizing plate; a first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate opposite to the first polarizing plate; a second transparent conductive layer formed on one surface of the second polarizing plate and opposite to the first transparent conductive layer; and a liquid crystal layer present between the first transparent conductive layer and the second transparent conductive layer, wherein the first polarizing plate may be characterized in that it comprises an ultraviolet blocking substrate, a polarizer, and a near-ultraviolet protective layer, and preferably, the first polarizing plate may be characterized in that an ultraviolet blocking substrate, a polarizer, and a near-ultraviolet protective layer are sequentially stacked from the outer side facing the light source.
[0056] According to one embodiment of the present invention, the above-mentioned laminated film may be characterized in that the transmittance at a wavelength of 360nm, 380nm and / or 400nm is as low as below 10%, preferably as low as below 9%, and more preferably as low as below 7%. In this case, the degradation of the liquid crystal layer can be prevented due to effective shielding of ultraviolet rays and / or near-ultraviolet rays, thereby providing high-quality smart windows and windows for automobiles or buildings using the same.
[0057] The variable transmittance optical laminate of the present invention is particularly suitable for the technical field in which the transmittance of light can be changed by application of voltage, and can be used, for example, in smart windows and the like.
[0058] The so-called smart window refers to an optical structure that changes the transmittance of light according to the application of an electrical signal to control the amount of light or heat passing through. In other words, a smart window can change to a transparent, opaque or semi-transparent state according to voltage, and is also called variable transmittance glass, dimming glass or smart glass.
[0059] Smart windows can be used as partitions for dividing the interior space of vehicles and buildings or partitions for privacy protection, or as daylight windows arranged at the openings of buildings. In addition, they can also be used as highway signs, bulletin boards, scoreboards, clocks or advertising screens, and can replace the glass of transportation tools such as windows or skylights of cars, buses, airplanes, ships or trains.
[0060] The variable transmittance optical laminate of the present invention can also be used as a smart window in the above fields. However, since the conductive layer is directly formed on the polarizing plate and does not include a separate substrate for forming the conductive layer, the thickness is thin, which is beneficial to the bending characteristics and can be particularly suitable for use in smart windows for vehicles or buildings. In one or more embodiments, the smart window using the variable transmittance optical laminate of the present invention can be used for the front window, rear window, side window and skylight of a car, or a window for a building, etc. In addition to the purpose of blocking external light, it can also be used for the internal space division of a car or a building, etc., or for privacy protection, such as an internal partition.
[0061] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the accompanying drawings. However, the following drawings attached to this specification are only examples of preferred embodiments of the present invention, which serve to further understand the above-mentioned invention content and the technical ideas of the present invention, so the present invention should not be interpreted only in accordance with the matters recorded in these drawings.
[0062] The terms used in this specification are intended to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular form also includes the plural form. For example, the "polarizing plate" used in this specification may refer to at least one of the first polarizing plate and the second polarizing plate, and the "transparent conductive layer" may refer to at least one of the first transparent conductive layer and the second transparent conductive layer.
[0063] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, actions and / or elements other than the mentioned constituent elements, steps, actions and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.
[0064] As illustrated in the accompanying drawings, spatially relative terms "below", "bottom", "lower", "above", "upper surface", "upper part", etc. can be used to easily describe the correlation between one element or constituent element and other elements or constituent elements. Spatially relative terms should be understood as terms that include different directions of the elements when in use or in operation in addition to the directions illustrated in the drawings. For example, when the elements illustrated in the drawings are turned over, the elements described as "below" or "lower" of other elements can be placed "above" other elements. Therefore, the exemplary term "below" can include both directions below and above. Elements can also be oriented in other directions, so spatially relative terms can be interpreted according to orientation.
[0065] In the present invention, the term "transparent" means that the transmittance of visible light is 70% or more or 80% or more.
[0066] In the present invention, "ultraviolet rays" refer to wavelengths of 100 to 390 nm, and "near ultraviolet rays" refer to wavelengths of 390 to 420 nm.
[0067] In the present invention, the terms "shield" and "block" mean to protect against the influence of ultraviolet rays or near-ultraviolet rays, and are used without distinction.
[0068] Reference Figure 1-2 The "outer side" used in this specification refers to the surface facing the incident direction A of the light source, which means the surface directly affected by ultraviolet rays or near-ultraviolet rays.
[0069] <Variable Transmittance Optical Laminate>
[0070] Figure 1 The structure of the first polarizing plate of one embodiment of the present invention is shown. Figure 2 FIG. 2 shows a preferred stacking structure of a variable transmittance optical stack according to an embodiment of the present invention. Figure 2 The variable transmittance optical laminate 100 of the present invention comprises: a first polarizing plate 110-1; a first transparent conductive layer 120-1 formed on one surface of the first polarizing plate; a second polarizing plate 110-2 opposite to the first polarizing plate; a second transparent conductive layer 120-2 formed on one surface of the second polarizing plate and opposite to the first transparent conductive layer; and a liquid crystal layer 130 between the first transparent conductive layer and the second transparent conductive layer. Figure 1 The first polarizing plate 110 - 1 may include an ultraviolet blocking substrate 111 , a polarizer 112 , and a near-ultraviolet protective layer 113 , and may further include a protective layer (protective film, not shown).
[0071] First polarizing plate 110 - 1
[0072] Reference Figures 1-2 The variable transmittance optical laminate of one embodiment of the present invention includes a first polarizing plate 110-1 formed on the outer side facing the light source A. The first polarizing plate 110-1 may include an ultraviolet blocking substrate 111, a polarizer 112, and a near-ultraviolet protective layer 113. More specifically, in order to take into account the use of ultraviolet curing adhesive to manufacture the polarizing plate and prevent the liquid crystal layer from being polluted by the overflow (bleed-out) of the absorbent, it is more preferred as follows Figure 1 As shown, an ultraviolet blocking substrate 111, a polarizer 112 and a near-ultraviolet protective layer 113 are stacked in order from the outer side facing the light source A.
[0073] Specifically, when a UV absorber and a near-UV absorber are mixed in the same substrate layer, there is a concern that the absorber may overflow (bleed-out) and contaminate the adjacent layers, so it is preferably added to different layers. On the other hand, when a UV-curable adhesive for bonding a polarizer protective film is used while protecting the polarizer from UV radiation, since UV radiation must be fully applied to cure the adhesive, at least one side of the polarizer needs to be permeable to UV radiation. Therefore, if Figure 1 As shown, the variable transmittance optical stack according to the stacking order of one embodiment of the present invention is not only intended to manufacture a structure using a UV-curable adhesive, but can also be regarded as the optimal stacking order for preventing UV degradation of the polarizing layer and the liquid crystal layer while preventing contamination caused by overflow of the absorber.
[0074] UV blocking substrate 111
[0075] According to one embodiment of the present invention, the first polarizing plate 110-1 includes an ultraviolet blocking substrate 111, which has an ultraviolet shielding function. In order to protect the polarizing layer and the liquid crystal layer from ultraviolet radiation at the same time, it is preferably formed in the direction facing the incident light source ( Figures 1-2 A) of the outer side. Specifically, from the perspective of effectively protecting the polarizing layer and the liquid crystal layer from ultraviolet rays, specifically from ultraviolet rays and near-ultraviolet rays, by including the above-mentioned ultraviolet blocking substrate, it is preferred that the transmittance at a wavelength of 380nm is 10% or less, and the wavelength in the ultraviolet band can be effectively blocked to ensure the curing degree of the coating. The ultraviolet blocking substrate of the present invention has an ultraviolet blocking function by including an ultraviolet blocking additive.
[0076] In addition to the ultraviolet blocking function, the ultraviolet blocking substrate 111 can also play the role of reducing impact and preventing damage to the internal substrate when damage such as impact and scratches are applied to the front of the laminate and / or the smart window containing it. Therefore, it is preferred that the material has a high tolerance to strain energy, for example, there is a release film formed by the following resins or a mixture of these resins: polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate; polyimide resins; acrylic resins; styrene resins such as polystyrene and acrylonitrile-styrene; polycarbonate resins; polylactic acid resins; polyurethane resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl resins such as polyvinyl chloride and polyvinylidene chloride; polyamide resins; sulfone resins; polyether-ether ketone resins; allyl resins; cellulose resins such as triacetyl cellulose. In particular, it may include one or more selected from polyester films, cellulose films, polyimide films and polycarbonate films. In one embodiment of the present invention, cellulose films are most preferred from the perspective of optical transparency and excellent durability against friction, heat and / or chemical damage. The thickness of the substrate using the cellulose resin may be used without limitation, but the thicker it is, the heavier it is and the worse it is in terms of handling. Therefore, 25 to 80 μm is preferred as a protective film.
[0077] According to one embodiment of the present invention, the ultraviolet blocking substrate has an ultraviolet blocking function by including an ultraviolet blocking additive. When the substrate includes an ultraviolet blocking additive, the degradation of the liquid crystal layer can be prevented by effectively shielding ultraviolet rays in the region below 400nm, and the lifespan shortening problem of the variable transmittance optical stack and the smart window including the same can be improved. The ultraviolet blocking additive can be a benzophenone compound, a benzotriazole, and a triazine compound, but is not limited thereto, and preferably contains 0.1% to 10% relative to the total weight of the composition forming the substrate.
[0078] The thickness of the ultraviolet blocking substrate 111 is not particularly limited, and may be, for example, 10 to 100 μm. When the thickness is within the above range, the handling property is excellent and it is preferable as a member of the smart window laminate.
[0079] Polarizer 112
[0080] In the variable transmittance optical laminate of one embodiment of the present invention, at least one of the first polarizing plate 110-1 and the second polarizing plate 110-2 may use a polarizer developed in the past or in the future. Preferably, the first polarizing plate 110-1 may be formed by sequentially stacking the above-mentioned ultraviolet blocking substrate 111, the polarizer 112, and the near-ultraviolet protective layer 113 described later. The above-mentioned polarizer may use, for example, a stretched polarizer or a coated polarizer.
[0081] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA) resin. The polyvinyl alcohol (PVA) resin may be a polyvinyl alcohol resin obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith may also be mentioned. As the other monomers mentioned above, unsaturated carboxylic acid series, unsaturated sulfonic acid series, olefin series, vinyl ether series, acrylamide series monomers having an ammonium group, etc. may be mentioned. In addition, the polyvinyl alcohol (PVA) resin includes modified substances, for example, polyvinyl formal or polyvinyl acetal modified by aldehydes may also be mentioned.
[0082] In one embodiment, the coating type polarizer may be formed by using a liquid crystal coating composition. In this case, the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.
[0083] The reactive liquid crystal compound described above for the reactive liquid crystal compound of the optical functional film can be applied in the same manner.
[0084] The dichroic dye is a component added to the liquid crystal coating composition to impart polarization characteristics, and has the property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. The dichroic dye can use dichroic dyes developed in the past or in the future, for example, it can include acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments, anthraquinone pigments, etc., which can be used alone or in combination.
[0085] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, and chloroform, etc. In addition, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc., within a range that does not hinder the polarization characteristics of the coating film.
[0086] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, and chloroform, etc. In addition, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc., within a range that does not hinder the polarization characteristics of the coating film.
[0087] The elastic modulus of the coating may be above 10 MPa, preferably 10 to 10 4 When the elastic modulus of the coating layer satisfies the above range, excellent adhesion and bendability can be exhibited.
[0088] In one embodiment, the coating layer may be formed from a photocurable coating layer-forming composition including a photopolymerizable compound and a photopolymerization initiator.
[0089] The above-mentioned photopolymerizable compound is not particularly limited as long as it allows the coating to exhibit the above-mentioned elastic modulus range. For example, acrylic monomers, epoxy monomers, vinyl ether monomers, oxetane monomers, etc. can be used. From the perspective of improving the elastic modulus, epoxy monomers, vinyl ether monomers, and oxetane monomers are preferably used. They can be used alone or in combination of two or more.
[0090] Examples of the acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, 2-methoxyethyl (meth)acrylate, (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and 1,2-diethylene glycol di(meth)acrylate. (Meth)acrylate, dipropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, isobornyl (meth)acrylate, N-vinylpyrrole Alkyl ketone, acryloyl morpholine, urethane (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, (meth) acrylate of mono-ε-caprolactone adduct of tetrahydrofurfuryl alcohol, (meth) acrylate of di-ε-caprolactone adduct of tetrahydrofurfuryl alcohol, (meth) acrylate of mono-ε-methyl-δ-valerolactone adduct of tetrahydrofurfuryl alcohol, (meth) acrylate of di-β-methyl-δ-valerolactone adduct of tetrahydrofurfuryl alcohol, ω-carboxy-polycaprolactone monoacrylate, dimethylaminoethyl acrylate, etc. These may be used alone or in combination of two or more.
[0091] Examples of the epoxy monomer include aromatic epoxy compounds, alicyclic epoxy compounds, and aliphatic epoxy compounds.
[0092] Examples of the aromatic epoxy compound include diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and phenoxyglycidyl ether.
[0093] Examples of the alicyclic epoxy compound include dicyclopentadiene dioxide, limonene dioxide, 4-vinylcyclohexene dioxide, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, and bis(3,4-epoxycyclohexylmethyl)adipate.
[0094] Examples of the aliphatic epoxy compound include 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, and polytetramethylene glycol diglycidyl ether.
[0095] Examples of the vinyl ether monomers include diethylene glycol divinyl ether, triethylene glycol divinyl ether, cyclohexyl vinyl ether, polyethylene glycol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, etc. These monomers may be used alone or in combination of two or more.
[0096] Examples of oxetane monomers include 2-ethylhexyloxetane, xylylenebisoxetane, 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyloxetane-3-yl)methoxymethyl]benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, bis(3-ethyl-3-oxetane-1-ylmethyl)ether, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, phenol novolac oxetane, and 1,3-bis[(3-ethyloxetane-3-yl)methoxy]benzene. These monomers may be used alone or in combination of two or more.
[0097] The photopolymerization initiator may be a cationic initiator or a radical initiator generally used in the art. Examples of the cationic initiator include onium salt compounds and iron-arene complexes.
[0098] Examples of the onium salt compound include aromatic diazonium salts such as benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate; aromatic iodonium salts such as diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate; triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, 4,4'-bis[diphenylsulfonium]diphenyl sulfide bishexafluorophosphate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide bishexafluoroantimonate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide bishexafluoroantimonate, -Aromatic sulfonium salts such as bis[di(β-hydroxyethoxy)phenylsulfonium]diphenyl sulfide bishexafluorophosphate, 7-[di(p-tolyl)sulfonium]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-tolyl)sulfonium]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonium-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-tolyl)sulfonium-diphenyl sulfide tetrakis(pentafluorophenyl)borate, and diphenyl[4-(phenylthio)phenyl]sulfonium phosphate; and the like.
[0099] Examples of the iron-arene complex include xylene-cyclopentadienyl iron (II) hexafluoroantimonate, cumene-cyclopentadienyl iron (II) hexafluorophosphate, and xylene-cyclopentadienyl iron (II)-tris(trifluoromethylsulfonyl)methanide.
[0100] Examples of the radical initiator include acetophenone-based, benzoin-based, benzophenone-based, thioxanthone-based, and triazine-based compounds, etc. These may be used alone or in combination of two or more.
[0101] Examples of the acetophenone compounds include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-[2-(2-hydroxyethoxy)phenyl]propane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane-1-one.
[0102] Examples of the benzoin-based compound include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0103] Examples of the benzophenone compounds include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4′-methyldiphenyl sulfide, 3,3′,4,4′-tetrakis(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0104] Examples of the thioxanthone compound include 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, and 1-chloro-4-propoxythioxanthone.
[0105] Examples of the triazine compounds include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-piperonyl-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[ 2-(5-methylfuran-2-yl)ethylidene]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethylidene]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethylidene]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethylidene]-1,3,5-triazine, etc.
[0106] The content of the photopolymerization initiator is not particularly limited, and may be, for example, 0.1 to 10 parts by weight relative to 100 parts by weight of the photopolymerizable compound. When the content is within the above range, the coating can be cured at an appropriate level to form a coating having the above elastic modulus range.
[0107] In one or more embodiments, the thickness of the coating may be 3 to 10 μm, more preferably 3 to 7 μm. If the thickness of the coating is less than 3 μm, the cohesive force and elastic modulus are reduced or it is difficult to embody the adhesion, especially the adhesion between the polarizer and the coating is reduced and the function of protecting the polarizer may be reduced. In addition, if the thickness of the coating is greater than 10 μm, a phase difference is generated and it is difficult to control the transmittance, especially the adhesion between the conductive layer and the coating is reduced and it may be difficult to form a conductive layer.
[0108] In one embodiment, the coating may further contain nanoparticles to improve the hardness and adhesion of the coating.
[0109] In one embodiment, at least one of the first polarizing plate 110-1 and the second polarizing plate 110-2 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm. In this case, a thin optical laminate can be manufactured while maintaining the optical properties of at least one of the first polarizing plate 110-1 and the second polarizing plate 110-2.
[0110] At least one of the first polarizer 110-1 and the second polarizer 110-2 may include a curved shape to manufacture an optical laminate having a curved surface. For example, it may be formed into a shape that is curved toward the side of any one of the two different polarizers 110-1 and 110-2 stacked on both sides of the liquid crystal layer 130.
[0111] Near UV protection layer 113
[0112] The near-ultraviolet protective layer 113 of the present invention is formed on one side of the polarizer 112 of the first polarizing plate 110-1, thereby playing a role in protecting the polarizer. Preferably, it can be located on the inner side that is not directly facing the light source (A). In this case, it has the advantages of preventing overflow (Bleed-out) while protecting the liquid crystal layer. The above-mentioned near-ultraviolet protective layer 113 may include a near-ultraviolet absorber with a maximum absorption wavelength of 390nm to 430nm. For example, it can be formed by curing by UV irradiation after being coated on the polarizer in the form of a composition. Specifically, ultraviolet rays can be transmitted and near-ultraviolet rays can be selectively absorbed by including one or more selected from near-ultraviolet absorbers and ultraviolet photosensitizers. In addition, it can further include photocurable resins, initiators, solvents, leveling agents, etc., which are commonly used in the technical field of the present invention to form a hard coating. In addition, its content can be variously adjusted within the range that does not reduce the physical properties of the variable transmittance optical laminate of the present invention, so there is no special restriction.
[0113] The above-mentioned near-ultraviolet absorber allows ultraviolet rays to pass through and selectively absorbs near-ultraviolet rays. The maximum absorption wavelength of the near-ultraviolet absorber of one embodiment of the present invention can be 390nm to 430nm, preferably 395nm to 425nm, and more preferably 400nm to 420nm. The above-mentioned near-ultraviolet absorber can be, for example, one or more selected from cyanine, benzophenone compounds, benzotriazole and triazine compounds. The cyanine derivative is the most suitable in effectively absorbing near-ultraviolet rays in the 390nm to 430nm region. In the case of a normal display, in order to allow the short wavelength region (blue) of visible light to pass through, 380nm is set as the upper limit boundary value for blocking ultraviolet rays. However, in the present invention, as a smart window laminate, its main function is to block or transmit external light (sunlight) shielding, so it is relatively insensitive to color changes caused by blocking part of the visible light region, so it has the advantage of being able to further expand the area that has not been shielded in the display due to the so-called inevitable issue of presenting natural colors to effectively prevent the degradation of polymers and / or low molecules in the liquid crystal layer.
[0114] The near ultraviolet absorber may be contained in an amount of 0.01 to 5 parts by weight, preferably 0.1 to 1 part by weight, and more preferably 0.3 to 0.7 parts by weight, relative to the total weight of the near ultraviolet protective layer composition.
[0115] The above-mentioned ultraviolet sensitizer performs the following functions: shielding ultraviolet rays by absorbing ultraviolet rays, and transferring energy (releasing after absorption) to the initiator described later contained in the hard coating composition through a photochemical reaction to promote the curing of the hard coating. Through such a series of photochemical reactions, it absorbs light in the ultraviolet region to keep the transmittance low, and at the same time induces the initiation reaction of the initiator that causes the cross-linking reaction of the ultraviolet curable material. The laminated film of one embodiment of the present invention can improve the adhesion with the substrate when it contains the above-mentioned ultraviolet sensitizer. According to one embodiment of the present invention, the maximum absorption wavelength of the above-mentioned ultraviolet sensitizer can be 350nm~400nm, preferably 355nm~395nm, and more preferably 360nm~390nm.
[0116] As the ultraviolet sensitizer as described above, for example, it can be one or more selected from oxazole, anthraquinone, naphthoquinone, quinone, thioxanthone, acridone, benzoyldiphenylphosphine oxide, 1,2-diketone, phenothiazine, coumarin ketone, fluorene, naphthiazoline, biacetyl, benzil and their derivatives, perylene and substituted / unsubstituted anthracene. Oxazole compounds are suitable from the perspective of being able to effectively absorb ultraviolet rays in the 350 to 400 nm region.
[0117] The content of the ultraviolet sensitizer may be 0.01 to 5 parts by weight, preferably 0.1 to 2 parts by weight, and more preferably 0.5 to 1.5 parts by weight, relative to the total weight of the near-ultraviolet protective layer composition.
[0118] Second polarizing plate 110 - 2
[0119] Except that the first polarizing plate 110 - 1 may or may not include an ultraviolet blocking substrate and a near-ultraviolet protective layer, the second polarizing plate 110 - 2 may directly apply the contents of the first polarizing plate 110 - 1 , and thus description thereof will be omitted.
[0120] In one or more embodiments, at least one of the first polarizing plate 110 - 1 and the second polarizing plate 110 - 2 may further include one or more functional layers selected from the group consisting of a functional coating, a protective layer, a phase difference adjustment layer and / or a refractive index adjustment layer.
[0121] The functional coating is provided to improve the hardness of the polarizing plate and is not particularly limited as long as it can improve the hardness of the polarizing plate. For example, it may include a hard coating layer and / or a low refractive index layer.
[0122] The hard coating composition may be formed from a hard coating composition comprising an acrylate or epoxy compound, inorganic particles, a photoinitiator, etc. The acrylate compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryl" used in this specification is used to refer to "methacryl-", "acryl-" or both. Non-limiting examples of the acrylate compounds include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and the like. (Meth) acrylate, dipentaerythritol penta (meth) acrylate, dipentaerythritol tetra (meth) acrylate, dipentaerythritol hexa (meth) acrylate, tripentaerythritol tri (meth) acrylate, tripentaerythritol hexa (meth) acrylate, bis (2-hydroxyethyl) isocyanurate di (meth) acrylate, hydroxyethyl (meth) acrylate, hydroxypropyl (meth) acrylate, hydroxybutyl (meth) acrylate, isooctyl (meth) acrylate, isodecyl (meth) acrylate, stearyl (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, phenoxyethyl (meth) acrylate or isobornyl (meth) acrylate, etc. They can be used alone or in combination of two or more. The above-mentioned acrylate compound can include epoxy (meth) acrylate compounds and / or carbamate (meth) acrylate compounds. In addition, the above-mentioned epoxy compound can include a monomer or oligomer having at least one epoxy group in the molecule. The above-mentioned epoxy group can be an alicyclic epoxy group. The carbon number of the alicyclic ring contained in the above-mentioned epoxy group can be 3 to 7, for example, it can be an alicyclic epoxy group (cyclohexyl epoxy group) containing a cyclohexane ring. The above-mentioned alicyclic ring may also have a substituent. For example, the above-mentioned alicyclic ring may contain an alkyl substituent having 1 to 20 carbon atoms. In the case where the carbon number of the above-mentioned alkyl substituent is greater than 20, it may be disadvantageous in terms of curing speed. The above-mentioned alkyl substituent includes a straight chain type or a branched type. In the case of a branched type, the carbon number can be 3 or more. On the other hand, in the hard coating preparation method of the present invention, in addition to the above-mentioned components, it can further contain additives commonly used in the technical field of the present invention such as photoinitiators, surfactants, anti-yellowing agents, leveling agents and / or antifouling agents. In addition, its content can be variously adjusted within the range that does not reduce the physical properties of the hard coating composition of the present invention, so there is no particular restriction.
[0123] The low refractive index layer may also play a role in improving the hardness of the polarizing plate within a range not impairing the purpose of the present invention. The low refractive index layer may include, for example, a material selected from SiO 2 、Al 2 O 3 MgF 2 , CaF and cryloite, etc., and in some embodiments, the hard coating layer and the low refractive index layer may be used alone or in a multilayer structure.
[0124] The functional coating can be formed by directly contacting one side of the polarizer, but is not limited thereto. For example, in the case where the polarizing plate includes a phase difference adjustment layer and / or a refractive index adjustment layer, the functional coating can be formed on one side of the phase difference adjustment layer and the refractive index adjustment layer, so that the functional coating, the phase difference adjustment layer, the refractive index adjustment layer and the polarizer are stacked in this order.
[0125] The functional coating is preferably formed on the liquid crystal layer side of the polarizer, that is, on the inner side of the polarizer, but is not limited thereto, and may also be formed on the outer side of the polarizer, so that the polarizer, the functional coating and the protective layer are stacked in this order. In this case, since the functional coating imparts a level of hardness suitable for forming a member such as a transparent conductive layer on the polarizing plate, it has the advantage of minimizing cracks or scratches generated during the manufacturing or processing process of the optical laminate.
[0126] The above-mentioned functional coating not only has excellent wear resistance, but also can further improve the bending resistance and durability of the optical stack. In more detail, it can more effectively suppress defects such as cracks in the conductive layer caused by the pressure applied by spacers in the bonding process of the optical stack or chemical reactions of liquid crystals, oriented films, etc.
[0127] In one or more embodiments, the thickness of the functional coating after drying may be 1 to 50 μm, more preferably 1 to 40 μm, but is not limited thereto.
[0128] The protective layer (not shown) is intended to protect the polarization characteristics of the polarizer from the influence of the subsequent process and the external environment, and can be implemented in the form of a protective film or the like. The protective layer can be formed by directly contacting one or both sides of the polarizer, but is not limited to this. For example, the protective layer can be used as a multilayer structure in which more than one protective layer is continuously stacked, or can be formed by directly contacting other components such as a phase difference adjustment layer. In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA) and cyclic olefin polymer (COP).
[0129] In addition, the protective layer may further contain an ultraviolet absorber on the outermost surface to prevent the function of the optical laminate from being reduced. The ultraviolet absorber is not particularly limited as long as it is used to prevent the degradation of the optical laminate caused by ultraviolet rays. For example, salicylic acid ultraviolet absorbers (phenyl salicylate, salicylic acid p-tert-butyl ester, etc.), benzophenone ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy -3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'- Hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-
[0043] The invention relates to a mixture of cyanoacrylate-based UV absorbers (a mixture of 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, etc.), triazine-based UV absorbers, etc., preferably a benzotriazole-based UV absorber or a triazine-based UV absorber which has high transparency and an excellent effect of preventing degradation of a substrate such as a polarizing plate, and particularly preferably a benzotriazole-based UV absorber having a more suitable spectral absorption spectrum. The above-mentioned benzotriazole-based ultraviolet absorber can also be a bis (Bis) substance, for example, it can be 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2,4,4-trimethylpentane-2-yl) phenol), 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2-hydroxyethyl) phenol), etc.
[0130] The protective layer is intended to protect the polarization characteristics of the polarizing plate from the influence of the subsequent process and the external environment, and can be implemented in the form of a protective film, etc. The protective layer can be used in a multilayer structure composed of more than one protective layer stacked continuously, or can be used in combination with other functional layers.
[0131] In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA) and cyclic olefin polymer (COP).
[0132] The above-mentioned phase difference adjustment layer is intended to supplement the optical properties of the optical laminate, and can be implemented in the form of a phase difference film, etc., and a phase difference film developed in the past or in the future can be used. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light can be used, and they can be used alone or in combination.
[0133] The phase difference adjustment layer may be formed by directly contacting one side of the polarizer, but is not limited thereto. For example, the phase difference adjustment layer may be formed by directly contacting one side of the protective layer, or may be formed by directly contacting one side of the refractive index adjustment layer.
[0134] The phase difference adjustment layer may be a stretched polymer film or a liquid crystal polymer film obtained by appropriately stretching a polymer film capable of imparting optical anisotropy.
[0135] In one embodiment, the above-mentioned polymer stretch film can use a polymer layer containing the following substances: polyolefins such as polyethylene (PE) or polypropylene (PP), cyclo olefin polymers (COP: cyclo olefin polymer) such as polynorbornene, polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resin (acryl resin), polycarbonate (PC), polyesters such as polyethyleneterephthalate (PET), polyacrylate, polyvinyl alcohol (PVA) or triacetyl cellulose (TAC) and other cellulose ester polymers, or copolymers of two or more monomers among the monomers forming the above-mentioned polymers, etc.
[0136] The method for obtaining the above-mentioned polymer stretch film is not particularly limited, for example, it can be obtained by stretching the above-mentioned polymer material after being molded into a film shape. The above-mentioned method of being molded into a film shape is not particularly limited, and can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and tape casting, or by secondary processing molding methods such as compression molding and vacuum molding. Among them, extrusion molding and tape casting are preferably used. At this time, for example, an extruder equipped with a T-shaped mold, a circular mold, etc. can be used to extrusion mold the unstretched film. In the case of obtaining a molded product by extrusion molding, a material that has been melt-mixed in advance with various resin components, additives, etc. can be used, and it is also possible to mold via melt mixing during extrusion molding. In addition, solvents shared by various resin components, such as chloroform, dichloromethane, etc., can be used to dissolve various resin components, and then tape casting, drying, and solidification are performed, thereby casting the unstretched film.
[0137] For the above-mentioned polymer stretched film, the above-mentioned formed film can be uniaxially stretched along the mechanical flow direction (MD; Mechanical Direction, longitudinal or length direction), uniaxially stretched along the direction perpendicular to the mechanical flow direction (TD; Transverse Direction, transverse or width direction), and can also be stretched by a sequential biaxial stretching method of roller stretching and tenter stretching, a simultaneous biaxial stretching method based on tenter stretching, a biaxial stretching method based on tubular stretching, etc. to produce a biaxially stretched film.
[0138] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be similarly applied to the reactive liquid crystal compound of the coating type polarizer.
[0139] In one or more embodiments, the thickness of the phase difference adjustment layer may be 10 to 100 μm in the case of a polymer stretched film in order to thin the optical laminate, and may be 0.1 to 5 μm in the case of a liquid crystal polymer film, but is not limited thereto.
[0140] The refractive index adjustment layer may be provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer, and may play a role in improving the visible characteristics by reducing the refractive index difference. In addition, the refractive index adjustment layer may also be provided to correct the color caused by the transparent conductive layer. On the other hand, in the case where the transparent conductive layers 120-1 and 120-2 described later have patterns, the refractive index adjustment layer may compensate for the transmittance difference between the patterned area and the non-patterned area where the pattern is not formed.
[0141] Specifically, the transparent conductive layer is stacked adjacent to other components having a different refractive index, and due to the difference in refractive index with other adjacent layers, a difference in light transmittance may be induced. In particular, when the transparent conductive layer is patterned, the problem of the pattern area and the non-pattern area appearing different may occur. Therefore, by including the refractive index adjustment layer, the refractive index can be compensated to reduce the difference in light transmittance of the optical laminate, and in particular, when the transparent conductive layer is patterned, the pattern area and the non-pattern area will not appear different.
[0142] In one embodiment, the refractive index of the refractive index adjustment layer can be appropriately selected according to the materials of the other adjacent components, preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, light loss caused by the huge refractive index difference between the other components and the transparent conductive layer can be prevented. The refractive index adjustment layer is not particularly limited as long as it can prevent the huge refractive index difference between the other components and the transparent conductive layer. The compounds used in the formation of the refractive index adjustment layer developed in the past or in the future can be used. For example, it can be formed by a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.
[0143] In addition to the above functional layers, the polarizing plates 110 - 1 and 110 - 2 may further include other functional layers to assist or enhance the characteristics of the polarizing plates. For example, in order to further improve the mechanical durability, an outer coating layer may be further included.
[0144] In one or more embodiments, the polarizing plates 110 - 1 and 110 - 2 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm. In this case, a thin optical laminate can be manufactured while maintaining the optical properties of the polarizing plates 110 - 1 and 110 - 2 .
[0145] Transparent conductive layers 120 - 1 and 120 - 2
[0146] The transparent conductive layers 120-1 and 120-2 are provided for driving the liquid crystal layer 130 described later and can be formed by directly contacting the polarizing plate. Figure 2 As shown, the first transparent conductive layer 120 - 1 and the second transparent conductive layer 120 - 2 may each be formed by directly contacting the first polarizing plate 110 - 1 and the second polarizing plate 110 - 2 .
[0147] In the past, optical laminates used to manufacture smart windows and the like were manufactured by forming a conductive layer for liquid crystal driving on one side of a substrate and bonding the other side of the substrate to a polarizing plate. However, the variable transmittance optical laminate of the present invention is characterized in that a conductive layer is directly formed on one side of a polarizing plate without including a separate substrate for forming the conductive layer, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.
[0148] In one embodiment of the present invention, the first transparent conductive layer 120-1 and the second transparent conductive layer 120-2 can be formed by direct evaporation on one side of the polarizing plates 110-1 and 110-2. At this time, in order to improve the adhesion with the polarizing plates 110-1 and 110-2, the transparent conductive layer can be formed by directly contacting the pre-treated surface of the polarizing plate after pre-treatment such as corona treatment or plasma treatment is performed on one side of the polarizing plate. The pre-treatment is not limited to corona treatment or plasma treatment, and a pre-treatment process developed in the past or in the future can be used within the scope that does not damage the purpose of the present invention.
[0149] In another embodiment, in order to improve the adhesion between the transparent conductive layers 120-1, 120-2 and the polarizing plate, an easy-adhesion layer (not shown) disposed on one side of the polarizing plate can be placed between them and then directly contacted with the polarizing plate. The easy-adhesion layer can use the adhesive and / or adhesive material described in the adhesive / adhesive layer in other components described later, but is not limited thereto.
[0150] The above-mentioned transparent conductive layers 120-1, 120-2 preferably have a transmittance of 50% or more with respect to visible light. For example, they may include one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based substances, conductive polymers, conductive inks and nanowires, but are not limited to these. Materials for transparent conductive layers developed in the past or in the future may be used.
[0151] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium tin zinc oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), fluorine tin oxide (FTO), and zinc oxide (ZnO). In addition, the metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of them, for example, may include silver-palladium-copper (APC) alloy or copper-calcium (CuCa) alloy. The carbon-based material may include one or more selected from the group consisting of carbon nanotubes (CNT) and graphene, and the conductive polymer may include one or more selected from the group consisting of polypyrrole, polythiophene, polyacetylene, poly(3,4-ethylenedioxythiophene) (PEDOT) and polyaniline, etc. The conductive ink may be an ink mixed with metal powder and a curable polymer binder, and the nanowire may be, for example, silver nanowire (AgNW).
[0152] In addition, the transparent conductive layers 120-1 and 120-2 may be formed of a structure of two or more layers by combining the above-mentioned materials. For example, in order to reduce the reflectivity of incident light and increase the transmittance, they may be formed of a two-layer structure including a metal layer and a transparent conductive oxide layer.
[0153] The transparent conductive layers 120-1 and 120-2 can be formed by methods commonly used in the art, for example, by coating processes such as spin coating, roller coating, rod coating, dip coating, gravure coating, curtain coating, die coating, spray coating, blade coating, kneader coating, etc.; printing processes such as screen printing, spray printing, inkjet printing, letterpress printing, gravure printing, lithography, etc.; and evaporation processes such as chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD), etc.
[0154] Liquid crystal layer 130
[0155] The liquid crystal layer 130 may adjust the transmittance of light incident from one or more directions according to an electric field, thereby changing a driving mode of the optical stack.
[0156] The liquid crystal layer 130 may include a liquid crystal compound, and may be located, for example, in a space provided by a sealant layer (not shown) and a spacer (not shown) between the first polarizing plate 110 - 1 and the second polarizing plate 110 - 2 in the light control region.
[0157] The liquid crystal layer 130 is characterized in that it is driven according to an electric field. The liquid crystal layer 130 may be located between the first polarizer 110-1 and the second polarizer 110-2 in the light control region of the optical laminate 100. In one embodiment, the liquid crystal layer 130 may be located in a space provided by a sealant (not shown) and a spacer (not shown) between the first polarizer 110-1 and the second polarizer 110-2 in the light control region. In addition, the liquid crystal layer 130 may adjust the transmittance of light incident from an external light source according to the electric field formed between the first transparent conductive layer 120-1 and the second transparent conductive layer 120-2.
[0158] The liquid crystal layer 130 may be driven by a liquid crystal driving method developed in the past or in the future, for example, a twisted nematic (TN) mode, a super twisted nematic (STN) mode, etc. may be used.
[0159] The liquid crystal layer 130 of another embodiment of the present invention may include one or more spacers selected from the group consisting of ball spacers and column spacers. Ball spacers are particularly preferred. There may be more than one ball spacer, preferably with a diameter of 1 to 10 μm. In addition, when viewed from a top view, from the perspective of improving user visibility and transmittance in a light-transmitting mode, the area occupied by the ball spacer in the liquid crystal layer 130 (i.e., the light adjustment region) is preferably 0.01 to 10% relative to the area of the liquid crystal layer 130, but is not limited thereto.
[0160] other
[0161] In one embodiment, the above-mentioned liquid crystal layer 130 may further include other components within the scope not impairing the purpose of the present invention, for example, it may further include a frame sealant, an orientation film, an adhesive / bonding layer and / or an ultraviolet light absorbing layer, which can be formed on both sides of the liquid crystal layer 130 containing the liquid crystal compound.
[0162] The frame sealant may include a curable resin as a base resin. As the base resin, a known UV curable resin or thermosetting resin that can be used for the frame sealant in the art may be used. The UV curable resin may be a polymer of a UV curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.
[0163] As the base resin of the above-mentioned frame-sealing glue, for example, an acrylate resin, an epoxy resin, a urethane resin, a phenol resin or a mixture of the above-mentioned resins can be used. In one embodiment, the above-mentioned base resin can be an acrylate resin, and the above-mentioned acrylate resin can be a polymer of an acrylic monomer. The above-mentioned acrylic monomer can be, for example, a multifunctional acrylate. In another embodiment, the above-mentioned frame-sealing glue can further include a monomer component in the base resin. The above-mentioned monomer component can be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate can refer to a compound having one acryloyl group, and a multifunctional acrylate can refer to a compound having more than two acryloyl groups. The above-mentioned curable resin can be cured by irradiation with ultraviolet rays and / or heating. Regarding the above-mentioned ultraviolet irradiation conditions or heating conditions, they can be appropriately implemented within the scope that does not damage the purpose of the present application. The above-mentioned frame-sealing glue can further include an initiator, such as a photoinitiator or a thermal initiator, as needed.
[0164] The frame sealant may be formed by a method commonly used in the art, for example, by applying the frame sealant to the periphery of the liquid crystal layer (ie, the inactive area) using a glue dispenser with a nozzle.
[0165] The above-mentioned alignment film is not particularly limited as long as it is used to add alignment to the liquid crystal compound. For example, the above-mentioned alignment film can be prepared by coating an alignment film coating composition containing an alignment polymer, a photopolymerization initiator and a solvent and curing it. The above-mentioned alignment polymer is not particularly limited, and polyacrylate resins, polyamic acid resins, polyimide resins, polymers containing cinnamate groups, etc. can be used, and polymers that can show alignment in the past or in the future can be used.
[0166] The above-mentioned adhesive / bonding layer can be formed using an adhesive or a pressure-sensitive adhesive, and preferably has appropriate adhesive strength to prevent peeling, bubbles, etc. during handling of the optical laminate, while also having transparency and thermal stability.
[0167] The adhesive may be an adhesive previously developed or developed in the future, for example, a photocurable adhesive may be used. The photocurable adhesive may be crosslinked and cured by exposure to active energy rays such as ultraviolet (UV) and electron beam (EB), thereby exhibiting strong adhesive force, and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, and the like.
[0168] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a cured film by forming a polymer bond through a photopolymerization reaction. Examples of the reactive oligomer that can be used include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, and the like.
[0169] The reactive monomer acts as a crosslinking agent and diluent for the reactive oligomer and affects the adhesive properties. Examples of the reactive monomer include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.
[0170] The photopolymerization initiator absorbs light energy and generates free radicals or cations to initiate photopolymerization. A suitable photopolymerization initiator may be selected and used according to the photopolymerizable resin.
[0171] The adhesive may be an adhesive previously developed or developed in the future, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinyl pyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive force and viscoelasticity, but in terms of ease of acquisition, it is preferably an acrylic adhesive, for example, it may contain a (meth)acrylate copolymer, a crosslinking agent, a solvent, etc.
[0172] The crosslinking agent may be any crosslinking agent developed in the past or in the future, and may include, for example, polyisocyanate compounds, epoxy resins, melamine resins, urea resins, dialdehydes, methylol polymers, and preferably polyisocyanate compounds.
[0173] The above-mentioned solvent may include a common solvent used in the field of resin compositions, for example, alcohol compounds such as methanol, ethanol, isopropanol, butanol, propylene glycol methoxy alcohol, ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, propylene glycol methoxy acetate, cellosolve compounds such as methyl cellosolve, ethyl cellosolve, propyl cellosolve, hydrocarbon compounds such as hexane, heptane, benzene, toluene, xylene, etc. Solvents such as these can be used. These solvents can be used alone or in combination of two or more.
[0174] The thickness of the adhesive / bonding layer can be appropriately determined according to the type of resin that functions as the adhesive / adhesive, the adhesive / bonding strength, the environment in which the adhesive / adhesive is used, etc. In one embodiment, in order to ensure sufficient adhesive / bonding force and minimize the thickness of the optical laminate, the adhesive / bonding layer can have a thickness of 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm.
[0175] The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent degradation of the optical laminate due to ultraviolet rays. For example, salicylic acid ultraviolet absorbers (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy- 3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, -3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(straight chain and side chain dodecyl)-4-methylphenol, octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-( The invention also includes a mixture of cyanoacrylate-based UV absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, etc.), triazine-based UV absorbers, etc., preferably a benzotriazole-based UV absorber or a triazine-based UV absorber which has high transparency and an excellent effect of preventing degradation of the polarizing plate or the transmittance variable layer, and particularly preferably a benzotriazole-based UV absorber having a more suitable spectral absorption spectrum. The above-mentioned benzotriazole-based ultraviolet absorber can also be a bis (Bis) substance, for example, it can be 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2,4,4-trimethylpentane-2-yl) phenol), 6,6'-methylenebis (2-(2H-benzo [d] [1,2,3] triazol-2-yl) -4- (2-hydroxyethyl) phenol), etc.
[0176] <Method for Manufacturing Variable Transmittance Optical Laminate>
[0177] The present invention includes the method for producing the variable transmittance optical layered body described above. The method for producing the variable transmittance optical layered body is not particularly limited, and the optical layered body can be produced using any bonding technology or the above-mentioned photolithography technology.
[0178] For example, when forming a conductive layer on the above-mentioned polarizing plate, the composition for forming a functional conductive layer can be coated on a triacetyl cellulose film or a cycloolefin polymer (COP), and then joined to a polyvinyl alcohol-based polarizer. Alternatively, a triacetyl cellulose film or a triacetyl cellulose film and a cycloolefin film can be joined to both sides of a polyvinyl alcohol-based polarizer (23 μm, KURARAY) by an adhesive, and then the functional conductive layer composition can be selectively coated on the surface of the triacetyl cellulose film or the cycloolefin film of the manufactured polarizing plate.
[0179] <Smart Window>
[0180] In addition to the optical laminate, the present invention includes a smart window having the optical laminate. In addition, the present invention includes a car in which the smart window is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition, and a window for a building having the smart window.
[0181] The automobile including the smart window of the present invention can use adhesion / adhesive to join vehicle glass on both sides of the optical laminate including the liquid crystal layer and the optical functional layer. For example, it can be manufactured by placing an adhesive film and vehicle glass on both sides of the optical laminate, and then heating for 10 to 20 minutes at a temperature of 90°C and about 1 bar or in a vacuum state using a press machine. It can also be manufactured by applying a resin on one side of the vehicle glass, vacuum bonding the vehicle glass on both sides of the optical laminate, and UV curing. The above-mentioned adhesive film may include ethylene vinyl acetate (EVA) film, polyvinyl butyral (PVB) film, etc., and the above-mentioned resin may include a storage modulus (G') of 10 3 ~10 5 Pa's OCR resin, etc.
[0182] In addition, building windows (window glass) can be joined to one or both sides of the above-mentioned optical laminate, window glass can be joined to one side of the optical laminate in a laminated manner to manufacture a smart window product for windows, or UV adhesive can be applied to both sides of the optical laminate and then the window glass is bonded together, followed by UV curing to manufacture a smart window product for windows.
[0183] Below, experimental examples including specific embodiments and comparative examples will be provided to help understand the present invention, but this is only to illustrate the present invention and does not limit the scope of the appended claims. It is obvious to a person skilled in the art that various changes and modifications can be made to the embodiments within the scope and technical idea of the present invention. Of course, such changes and modifications also fall within the scope of the appended claims.
[0184] Production Example 1: Production of near-ultraviolet protective layer composition
[0185] 50.8 parts by weight of hexafunctional urethane acrylate (UA-306I, Kyoeisha), 44.6 parts by weight of butyl acetate, 3.3 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.3 parts by weight of a silicone leveling agent (BYK, BYK-UV3530), 0.5 parts by weight of a near-ultraviolet absorber (FDB-009 (λmax=402nm), Yamada Co., Ltd.), and 0.5 parts by weight of an ultraviolet sensitizer (NF-NA-01 (λmax=379nm), Nippon Chemical Works Co., Ltd.) were blended using a stirrer and filtered using a PP filter to prepare a near-ultraviolet protective layer composition.
[0186] Manufacturing Example 2: Manufacturing of the First Polarizing Plate
[0187] The first polarizing plate is manufactured by performing the following steps (1) to (7) in order.
[0188] (1) Swelling treatment process
[0189] A 60 μm thick polyvinyl alcohol (PVA) film (Kuraraypoval film VF-PE#6000, average polymer 2400, saponification degree 99.9 mol%) as a raw material film was continuously unwound from a raw material roll while being conveyed and immersed in a swelling bath containing pure water at 20°C for 30 seconds. Next, inter-roll stretching (uniaxial longitudinal stretching) was performed by generating a difference in circumferential speed between the nip rolls. The stretching ratio based on the raw material film was set to 2.5 times.
[0190] (2) Dyeing process
[0191] The film passed through the nip rolls of (1) was immersed in a dyeing bath at 30°C with a mass ratio of pure water: potassium iodide: iodine: boric acid of 100:2:0.01:0.3 for 120 seconds. Next, inter-roll stretching (uniaxial longitudinal stretching) was performed by creating a difference in peripheral speed between the nip rolls. The stretching ratio based on the film after the swelling treatment step was set to 1.1 times.
[0192] (3) Cross-linking treatment process
[0193] The film passed through the nip roller of (2) was immersed in a first crosslinking bath at 56°C with a mass ratio of pure water: potassium iodide: boric acid of 100:12:4 for 70 seconds. Inter-roll stretching (uniaxial longitudinal stretching) was performed by creating a difference in peripheral speed between the nip roller and the nip rollers provided in the first crosslinking bath and the second crosslinking bath. The stretching ratio based on the film after the dyeing treatment step was set to 1.9 times.
[0194] (4) Color correction process
[0195] The cross-linked film was immersed in a second cross-linking bath at 40° C. with a mass ratio of pure water: potassium iodide: boric acid of 100:9:2.9 for 10 seconds.
[0196] (5) Cleaning process
[0197] The membrane after the second crosslinking treatment was immersed in pure water at 14°C in a cleaning bath for 5 seconds with a washing volume of 5 m 3 / h and elution temperature of 14°C for cleaning.
[0198] (6) Drying process
[0199] In order to heat-dry the washed film, it was passed through a drying oven at 80° C. for 190 seconds. The polarizer film that had been heat-dried had a moisture content of 13.6% and a thickness of about 21 μm.
[0200] (7) Joining process
[0201] A water-based adhesive containing 5 parts by mass of PVA relative to 100 parts by mass of water was manufactured. A UV blocking substrate (80 μm, TAC film, Hyosung Corporation) and a protective film (80 μm, ZRT film, Hyosung Corporation) were laminated on both sides of the polarizer film obtained by the above (6) using the water-based adhesive. The obtained laminate was exposed to UV light to cure the adhesive, thereby manufacturing a first polarizing plate. The thickness of the adhesive layer after UV exposure was about 2 μm.
[0202] Production Example 3: Formation of near-ultraviolet protection layer
[0203] The near-ultraviolet protective layer composition of the above-mentioned Production Example 1 was applied to the polarizing plate of the above-mentioned Production Example 2 so that the thickness after curing would be 6 μm, and then the solvent was dried and the UV cumulative light amount was 500 mJ / cm in a nitrogen atmosphere. 2 The irradiation is performed to form a near-ultraviolet protective layer.
[0204] Manufacturing Example 4: First Transparent Conductive Layer Vapor Deposition - Manufacturing of First Laminated Body
[0205] The first polarizing plate formed with the near-ultraviolet protective layer obtained in Manufacturing Example 3 was placed, and a 450 WDC power supply was applied to start the sputtering gun, and then plasma was induced to the ITO (10 wt % Sn doped In 2 O 3 ) target, thereby forming a transparent conductive layer (ITO layer) with a thickness of 40nm on the above-mentioned near-ultraviolet protective layer. The transparent conductive layer was ionized by starting an ion gun with a DC power of 50W to produce a first laminate including a first polarizing plate and a first transparent conductive layer. At this time, the pressure at room temperature was maintained at 3mTorr, and argon and oxygen were supplied at 30sccm and 1sccm, respectively.
[0206] Production Example 5: Production of the Second Laminated Body
[0207] A second laminate including a second polarizing plate and a second transparent conductive layer manufactured in the same manner as in the above-mentioned Manufacturing Examples 2 and 4 was manufactured except that the ultraviolet blocking substrate and the near ultraviolet protective layer were not included.
[0208] Manufacturing Example 6: Alignment Film Formation
[0209] An alignment liquid (RN-4662, Nippon Chemical Industry) was applied on the first transparent conductive layer obtained in Production Example 4 and the second transparent conductive layer obtained in Production Example 5, and then dried at 80° C. for 2 minutes. The dried alignment liquid was then irradiated with UV to form an alignment film.
[0210] Manufacturing Example 7: Spherical Spacer Dispersion
[0211] First, 0.03 g of spherical spacers (SEKISUI Co., Ltd., SP series) were mixed in 100 ml of isopropyl alcohol (IPA) to prepare a mixed solvent. Next, the second laminate of Manufacturing Example 5 was placed in a spacer dispenser (Shinto Giken Co., Ltd., SDSS-KHU02), the mixed solvent was dispensed at 110° C. and then dried for 20 minutes, thereby forming spherical spacers on the alignment film.
[0212] Manufacturing Example 8: Frame Sealing Adhesive, Liquid Crystal Layer Formation and Bonding - Manufacturing of Variable Transmittance Optical Laminated Body
[0213] On the second transparent conductive layer of the second laminate formed with an oriented film in Manufacturing Example 6, a frame sealant (Photolec S, Sekisui Co., Ltd.) with a viscosity of 250,000 mPa·s is applied into the recessed portion using a sharp needle (PN-17G, MUSASHI Co., Ltd.) and a frame sealant applicator (SHOTmini 200Ωx, MUSASHI Co., Ltd.) at a discharge pressure of 200 mPa. Liquid crystal is injected into the oriented film of the second laminate by One Drop Filling (ODF). Next, the polarization axes of the first polarizer and the second polarizer are arranged parallel to each other at 0° or 90°, and the first laminate and the second laminate are placed at 3 Kg / cm 2 Pressure bonding, followed by UV curing along the sealing glue line (500mJ / cm 2 ), thereby producing a variable transmittance optical stack.
[0214] Example 1
[0215] The variable transmittance optical layered body of Production Example 8 was applied to Example 1.
[0216] Example 2
[0217] In the first polarizing plate, a variable transmittance optical laminate similar to that of Example 1 was produced except that the protective layer was located on the opposite side of the liquid crystal layer and the transparent conductive layer was formed on the ultraviolet blocking substrate.
[0218] Comparative Example 1
[0219] In the (7) bonding treatment step of the above-mentioned manufacturing example 2, a protective film (80μm ZRT film (TAC film other than UV-TAC (ultraviolet blocking substrate)), manufactured by Hyosung Corporation) is used instead of the ultraviolet blocking substrate, and a separate near-ultraviolet protective layer is not included. Otherwise, a variable transmittance optical stack having the same structure as that of Example 1 is manufactured.
[0220] The structures of the variable transmittance optical laminates of Example 1, Example 2 and Comparative Example 1 are summarized and described in Table 1 below.
[0221] [Table 1]
[0222]
[0223] Experimental example
[0224] (1) Lightfastness evaluation
[0225] The variable transmittance optical stacks of the embodiments and comparative examples were prepared and arranged in the order of light source / 2.0T soda-lime glass / variable transmittance optical stack. Based on Example 1, the ultraviolet blocking substrate of the first polarizing plate of the variable transmittance optical stack was directed toward the outer side, i.e., the light source, and light was irradiated according to the following conditions.
[0226] -Light source: Carbon Arc Lamp-type
[0227] -Radiant illumination: 500W / m 2 (Wavelength: 300nm~700nm)
[0228] -Test time: 1500 hours
[0229] - Temperature: 70℃
[0230] The opaque state (voltage on) after the above light resistance condition was observed, and the light resistance was evaluated according to the following criteria and is shown in Table 1 above.
[0231] <Evaluation Criteria>
[0232] ○: Keep opaque ( Figure 3a )
[0233] Δ: Some light leakage was confirmed ( Figure 3b )
[0234] X: Confirmed that the entire surface is leaking light ( Figure 3c )
[0235] According to the experimental data in Table 1, in the case where the variable transmittance optical laminate of the present invention is an embodiment in which the first polarizing plate of the first laminate includes an ultraviolet blocking substrate and a near-ultraviolet protective layer, compared with the comparative example in which light leakage is confirmed on the entire surface because the ultraviolet blocking substrate and the near-ultraviolet protective layer are not included (refer to Figure 3c ), almost no light leakage was observed during the light resistance evaluation. In particular, compared with Example 2 in which the near-ultraviolet protection layer is located on the outer side facing the light source (reference Figure 3b ), the ultraviolet blocking substrate is located on the outer side, so that the ultraviolet blocking substrate, the polarizer and the near-ultraviolet protection layer are stacked in sequence. Even when a voltage is applied, there is no light leakage, and the opaque state is maintained, showing a more excellent result in the light resistance evaluation (refer to Figure 3a ).
[0236] Therefore, the variable transmittance optical layered body of the present invention can prevent degradation of the liquid crystal layer due to ultraviolet rays, and a high-quality smart window can be provided by including the variable transmittance optical layered body.
Claims
1. A variable transmittance optical stack, comprising: a first polarizing plate; A first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate, which is opposite to the first polarizing plate; A second transparent conductive layer formed on one side of the second polarizing plate and opposite to the first transparent conductive layer; as well as a liquid crystal layer, which exists between the first transparent conductive layer and the second transparent conductive layer, The first polarizing plate comprises an ultraviolet blocking substrate, a polarizer and a near ultraviolet protective layer. 2 . The variable transmittance optical stack according to claim 1 , wherein the first polarizing plate is formed on an outer side surface facing the light source.
3. The variable transmittance optical laminate according to claim 2, It is characterized in that The first polarizing plate is sequentially stacked with an ultraviolet blocking substrate, a polarizer and a near-ultraviolet protective layer from the outer side facing the light source.
4. The variable transmittance optical laminate according to claim 1, It is characterized in that The ultraviolet blocking substrate has a transmittance of 10% or less at wavelengths below 380 nm.
5. The variable transmittance optical laminate according to claim 1, It is characterized in that The UV blocking substrate includes a UV blocking additive.
6. The variable transmittance optical laminate according to claim 1, It is characterized in that The ultraviolet blocking substrate includes one or more selected from the group consisting of a polyester film, a cellulose film, a polyimide film, and a polycarbonate film. 7 . The variable transmittance optical laminate according to claim 1 , wherein the near-ultraviolet protection layer comprises at least one selected from a near-ultraviolet absorber and an ultraviolet sensitizer.
8. The variable transmittance optical laminate according to claim 7, It is characterized in that The near-ultraviolet absorber has a maximum absorption wavelength of 390 nm to 430 nm.
9. The variable transmittance optical laminate according to claim 8, It is characterized in that The near ultraviolet absorber is a cyanine compound.
10. The variable transmittance optical laminate according to claim 7, It is characterized in that The maximum absorption wavelength of the ultraviolet sensitizer may be 350nm to 400nm.
11. The variable transmittance optical laminate according to claim 10, It is characterized in that The ultraviolet sensitizer is an oxazole compound. 12 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate comprises one or more functional layers selected from the group consisting of a functional coating layer, a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer. 13 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm. 14 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed to be in direct contact with one of the first polarizing plate and the second polarizing plate without including a separate substrate therebetween. 15 . The variable transmittance optical laminate according to claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed to be in direct contact with one of the first polarizing plate and the second polarizing plate by further including an easy-adhesion layer therebetween.
16. The variable transmittance optical stack according to claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires. 17 . The variable transmittance optical stack according to claim 1 , wherein the liquid crystal layer includes one or more spacers selected from the group consisting of spherical spacers and columnar spacers. 18 . The variable transmittance optical stack according to claim 1 , further comprising at least one selected from the group consisting of a frame sealant, an alignment film, an adhesive / bonding layer, and an ultraviolet light absorbing layer.
19. A method for producing the variable transmittance optical layered body according to any one of claims 1 to 18. 20 . A smart window comprising the variable transmittance optical laminate according to claim 1 .
21. A vehicle comprising the smart window according to claim 20.
22. An automobile, wherein the smart window according to claim 20 is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition.
23. A wearable device comprising the smart window according to claim 20.
24. A building window, comprising the smart window according to claim 20.
